The diversity and function of sourdough starter microbiomes - Landis, Elizabeth A; Oliverio, Angela M; McKenney, Erin A; Nichols, Lauren M; Kfoury, Nicole; Biango-Daniels, Megan; Shell, Leonora K; Madden, Anne A; Shapiro, Lori; Sakunala, Shravya; Drake, Kinsey; Robbat, Albert; et al. (eLife, 2021)
Humans have relied on sourdough starter microbial communities to make leavened bread for thousands of years, but only a small fraction of global sourdough biodiversity has been characterized. Working with a community-scientist network of bread bakers, we determined the microbial diversity of 500 sourdough starters from four continents. In sharp contrast with widespread assumptions, we found little evidence for biogeographic patterns in starter communities. Strong co-occurrence patterns observed in situ and recreated in vitro demonstrate that microbial interactions shape sourdough community structure. Variation in dough rise rates and aromas were largely explained by acetic acid bacteria, a mostly overlooked group of sourdough microbes. Our study reveals the extent of microbial diversity in an ancient fermented food across diverse cultural and geographic backgrounds.
Keywords: sourdough; bacteria; fungi; microbial community